Study of relationship between personal causal factors and students’ academic performances / Faizal Yusak et al. - Yusak, Faizal; Zahari, Mohd Azri; Nordin, Muhammad Afiq; Eshbil, Muhammad Fadli (2012)
Many studies had been conducted on factors that affect students’ academic performances in universities. These studies are critical in ensuring better development and understanding of the study system and the nature of the higher education. The students’ performance (academic achievement) plays an important role in producing the best quality graduates who will become great leader and manpower for the country thus responsible for the country’s economic and social development. Thus, students’ academic performance is an important thing that should be continuously improved and given a great concern. Plenty of studies has been made on personal factors that affecting students performance in Universities and IPTAs, locally in Malaysia and internationally. There are several factors that had been studied which have correlations with IPTA’s students’ academic performance. There are a lot of causal factors to name regarding students’ academic performances. However, this study was made up to find the relationship between the motivational, financial, and time management causal factors and the students’ academic performances. In order to run the study, the data was collected through the distribution of self-administered-questionnaires to the students of Bachelor’s Degree in Office System Management in UiTM Dungun Terengganu. The result of this study has shown that all the factors studies (motivational, financial and time-management) affects the students’ academic performances. As the conclusion, this study found that all the variables (financial, time management and motivational causal factors) do contribute to the academic performances of the students in UiTM Dungun campus. The result also indicates that the most affecting causal factor out of the three is the motivational causal factor. Based on the result gained by the researchers through this study, the researchers’ recommendations go out to all parties that relate to the students’ academic performances and also to the future researchers who would like to further enhance this study. As for all party, it is important for them to realize that these causal factors exist and are affecting students’ academic performances and they should start building awareness on it. The researchers suggested that future researchers to either focus and study deeper on one variable or study more variables that affecting students’ academic performances.